Emergence of babesiosis in China-Myanmar border areas - Xia Zhou; Shang Xia; Shou-Qin Yin; Xiao-Nong Zhou (Parasites & Vectors, 2015)
Abstract E. Vannier and P. J. Krause presented an excellent article on “Babesiosis in China, an emerging threat” in the Lancet Infectious Diseases in December 2014, which updated research on human babesiosis in China. However, a neglected and emerging issue has not been mentioned in EV & PJK’s article, that is the co-infections with B. microti and P. falciparum parasites that exist in syndemic areas, spatially in the China-Myanmar border areas of Yunnan province, China. Therefore, two important issues are addressed in here, including (i) the new emerging infections with Babesia spp. which are normally ignored in malaria endemic areas due to similarities in pathogenic morphology and clinical symptoms, (ii) additional consideration on babesiosis rather than drug-resistant malaria when anti-malaria treatment for the febrile cases in clinics fails.